High temperature PEM fuel cell integrated with a cellular membrane methanol steam reformer: Experimental and modelling - Paulo Ribeirinha (2018)
In this work, the methanol steam reforming catalyst was considered into the anodic compartment of a high temperature polymer electrolyte fuel cell (HT-PEMFC), where reforming and electrochemical, reactions occur simultaneously. To avoid the anode electro-catalyst poisoning by methanol, a Pd-Ag membrane, with a thickness of a few micrometres, was considered between the reforming catalyst and the membrane electrode assembly. A 3-dimensional non-isothermal simulator was developed in Fluent (Ansys (TM)) considering a packed bed membrane reactor cell (PBMR-C) combined with a HT-PEMFC in a single unit. The performance of the combined unit depends on the permeability, selectivity and stability of Pd-Ag membrane at 473 K. Therefore, a self-supported Pd-Ag membrane with a thickness of 4 was produced with no defects by magnetron sputtering. The membrane showed a H-2/N-2 molar selectivity of ca. 5800 and permeability of 2.94 x 10(-6) mol/m.s(-1).m(-2).bar(-0.8) at 473 K. The novel PBMR-C/HT-PEMFC after proper validation was analysed by simulation, showing high performance, similar to the one obtained with a HT-PEMFC fed with hydrogen and allowed efficient heat integration between electrochemical and MSR reaction. The PBMR-C/HT-PEMFC also demonstrated to be very compact. The advantageous and limitations of the combined PBMR-C/HT-PEMFC unit are discussed based on the simulated results.